Pesan Dakwah dalam Film Mencari Hilal Karya Ismail Basbeth (Analisis Semiotika Roland Barthes) - Umam, Faizol; Wazis, Kun (Icon: Islamic Communication and Contemporary Media Studies, 2023)
Dakwah conveying the message of Islamic teachings. Dakwah at this time can be through mass media such as film, the movie Mencari Hilal has an interesting da'wah message. When determining 1 Syawal there are often pros and cons, such as Muhammadiyah, NU and the Government. Even though this film has been released for a long time, until now the movie Mencari Hilal is still being watched. The focus of the research: 1. What is the meaning of denotation, connotation, and myth in the movie Mencari Hilal in Roland Barthes' semiotic analysis? 2. What is the missionary message in the movie Mencari Hilal? Objectives: 1. To find out the meaning of denotation, connotation, and myths in the movie Mencari Hilal, 2. To find out the meaning of the da'wah message in the movis Mencari Hilal. The research method uses a qualitative approach. The theory used is Roland Barthes' semiotic analysis. To obtain data, researchers used observation techniques, interviews and documentation. The results of this study the researcher found the conclusion that the meaning of the denotation in the movie Mencari Hilal of the character Mahmud and his son, namely Heli, to look for the new moon. The mythical meaning of the film Islam teaches us to always have faith in Allah SWT. The message of Dakwah in the film Finding the Hilal is Faith in Allah SWT, prayer, fasting, reminding each other, at-tafaul (optimism), deliberation, ta’awun (mutual help).